The Effect of Organizational Commitment and Emotional Intelligence on Organizational Citizenship Behavior (OCB) Mediated by Work Motivation at PT. Legenda Bintang Bola in Karanganyar - Novi Fitriani; Jati Waskito (Jurnal Economic Resource, 2026)
The findings of this study imply that organizations, specifically PT. Legenda Bintang Bola—can strengthen Organizational Citizenship Behavior (OCB) by enhancing organizational commitment and emotional intelligence among employees. Since both variables also increase work motivation, and motivation itself positively influences OCB, the company should focus on programs that nurture employees’ emotional awareness, loyalty, sense of belonging, and overall engagement at work. In practical terms, the organization may benefit from implementing training related to emotional regulation, team-building activities to deepen commitment, and supportive policies that boost internal motivation. Strengthening these areas can help create a more collaborative, proactive, and productive workforce, ultimately improving organizational performance and stability.